2023
DOI: 10.3390/toxins15040255
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Metabolomics and Lipidomics Analysis Reveals Lipid Metabolic Disorder in NCM460 Cells Caused by Aflatoxin B1 and Aflatoxin M1 Alone and in Combination

Abstract: Aflatoxin B1 (AFB1) and aflatoxin M1 (AFM1) are universally found as environmental pollutants. AFB1 and AFM1 are group 1 human carcinogens. Previous sufficient toxicological data show that they pose a health risk. The intestine is vital for resistance to foreign pollutants. The enterotoxic mechanisms of AFB1 and AFM1 have not been clarified at the metabolism levels. In the present study, cytotoxicity evaluations of AFB1 and AFM1 were conducted in NCM 460 cells by obtaining their half-maximal inhibitory concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…Metabolomics data showed that glycerophospholipid metabolism is significantly disrupted by AFB 1 , as evidenced in one of the most affected KEGG pathways. Phospholipid small molecules, including phosphatidylethanolamine (PE), phosphatidylserine (PS), phosphatidylglycerol (PG), and 2-lysophosphatidylcholine (LysoPC), are essential components cellular membranes, playing vital roles in protein recognition, signaling, and cellular protection from external influences . Notably, phosphatidylglycerol and phosphatidylglycerophosphate (PGP), as precursors to cardiolipin, are crucial in repairing impaired mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics data showed that glycerophospholipid metabolism is significantly disrupted by AFB 1 , as evidenced in one of the most affected KEGG pathways. Phospholipid small molecules, including phosphatidylethanolamine (PE), phosphatidylserine (PS), phosphatidylglycerol (PG), and 2-lysophosphatidylcholine (LysoPC), are essential components cellular membranes, playing vital roles in protein recognition, signaling, and cellular protection from external influences . Notably, phosphatidylglycerol and phosphatidylglycerophosphate (PGP), as precursors to cardiolipin, are crucial in repairing impaired mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al, 2018). In addition to hepatic toxicity, renal toxicity is a noticeable medical disorder observed due to the aflatoxins AFB 1 and AFM 1 (H. Yang et al, 2023). AFB 1 triggers renal injury in mice and leads to pathological changes and renal dysfunction.…”
Section: Renal Toxicitymentioning
confidence: 99%
“…Oxidative stress is an important molecular mechanism for kidney injury in AFB1 nephrotoxicity [ 46 ]. It has been reported that AFB1 increases the production of ROS [ 47 ].…”
Section: Aflatoxin Metabolism and Toxicitymentioning
confidence: 99%